Point-of-care ultrasound abnormalities in late onset severe preeclampsia: prevalence and association with serum albumin and brain natriuretic peptide - Neethling, Elmari (Department of Anaesthesia and Perioperative Medicine, 2019)
Abstract Background: Pilot studies applying point-of-care ultrasound (POCUS) in preeclampsia indicate the presence of pulmonary interstitial edema, cerebral edema, and cardiac dysfunction. Laboratory markers of oncotic pressure (albumin) and cardiac dysfunction (brain natriuretic peptide [BNP]) may be abnormal, but the clinical application remains unclear. We investigated the prevalence of pulmonary interstitial syndrome (PIS), cardiac dysfunction, and increased optic nerve sheath diameter (ONSD) in late onset preeclampsia with severe features. The primary aim was to examine the association between PIS or ONSD and maternal serum albumin level. The secondary aims were to explore the association between cardiac dysfunction and PIS, ONSD, BNP, and serum albumin level, and between POCUS-derived parameters and a suspicious or pathological cardiotocograph (CTG). Methods: Ninety-five women were enrolled in this prospective observational cohort study. A POCUS examination of lungs, heart and ONSD was performed. PIS was defined as a bilateral B-line pattern on lung US, and diastolic dysfunction according to an algorithm of the American Society of Echocardiography. ONSD > 5.8 mm was interpreted as compatible with raised intracranial pressure (> 20 mmHg). Serum BNP and albumin levels were also measured. Results: PIS, diastolic-, systolic dysfunction, and raised left ventricular end-diastolic pressure (LVEDP) were present in 23 (24%,) 31 (33%), 9 (10%), and 20 (25%) women respectively. ONSD was increased in 27 (28%) women. Concerning the primary outcome, there was no association between albumin level and PIS (p = 0.4) or ONSD (p=0.63). With respect to secondary outcomes, there was no association between albumin level and systolic dysfunction (p = 0.21) or raised LVEDP (p = 0.44). PIS was associated with diastolic dysfunction (p = 0.02), and raised LVEDP (p = 0.009, negative predictive value 85%). BNP level was associated with systolic (p < 0.001)- and diastolic dysfunction (p = 0.003) and LVEDP (p = 0.007). No association was found between POCUS abnormalities and a suspicious/pathological CTG (p = 0.07). Conclusion: PIS, diastolic dysfunction and increased ONSD were common in preeclampsia with severe features. Cardiac ultrasound abnormalities may be more useful than albumin levels in predicting PIS. The absence of PIS may exclude raised LVEDP. The further clinical relevance of PIS and raised ONSD remains to be established. BNP level was associated with cardiac ultrasound abnormalities. Although this study was not designed to directly influence clinical management, the findings suggest that POCUS may serve as a useful adjunct to clinical examination for the obstetric anesthesiologist managing these complex patients.